Assessment of Pain and Stress Intensity among Women with Ovarian Endometriomas versus Teratomas - Karolina Chmaj-Wierzchowska; Małgorzata Kampioni; Maciej Wilczak; Stefan Sajdak; Tomasz Opala (Pain Research and Management)
BACKGROUND: In recent years, numerous studies have considered endometriosis to be a subclinical, local inflammatory process in the pelvic peritoneum, the main symptom of which is pain.